Museum Specimens Reveal the Taxonomic Distinctions Among South Asian Treeshrews - Manokaran Kamalakannan; Mukesh Thakur; Nithyanandam Marimuthu; Subhojit Pramanik; Dhriti Banerjee (Ecology and Evolution)
ABSTRACT South Asian treeshrews include the Madras Treeshrew Anathana ellioti, the Northern Treeshrew Tupaia belangeri, and the Nicobar Treeshrew Tupaia nicobarica, each occupying distinct and non‐overlapping geographical areas in India and Southeast Asia. In this study, we investigated the morphological variation among these species using museum specimens collected over a wide spatial and temporal range of India and Myanmar and combined with existing published datasets. We analyzed 22 cranial measurements and four external traits to evaluate inter‐ and intraspecific morphological differentiation, employing distance‐based morphometric approaches validated by multivariate analyses. Our findings revealed considerable heterogeneity in cranial morphology, with three species exhibiting clear differentiation, despite slight overlaps in morphospace. Furthermore, our results support the synonymy of the five previously recognized allopatric subspecies of T. belangeri and the two subspecies of A. ellioti. The additional diagnostic characteristics identified in this study enhance the understanding of morphological distinctions among the South Asian treeshrews and contribute to broader taxonomic knowledge of treeshrew diversity.